Analysis of consumer preferences for information and expert opinion using a discrete choice experiment - Ribeiro, Tiago (2020)
We present a study of consumer preferences for information in wine purchases. Consumers are presented with extra information in the form of qualitative product descriptions and quantitative expert ratings. We implement a discrete choice exper- iment in which we vary experimentally the presence of the descriptions and ratings and the values of the ratings themselves. Respondents are asked to choose amongst a set of 5 wine bottles in a sequence of 21 choice scenarios. We find that the presence of extra information and high expert ratings have a significant impact on the will- ingness to pay for a given wine. The dispersion of ratings for a given wine does not affect respondents’ choices. In our estimates high average ratings by experts carry a premium of AUD $10.